Analisis Dampak Kebakaran Pasar terhadap Keuntungan Pedagang di Pasar Induk Weleri Kabupaten Kendal - Khoirun Nisa; Evi Yulia Purwanti (Universitas Diponegoro, 2023)
This research aims to determine the effects of initial capital, education, working hours, and business location on the profits of traders in Weleri Central Market, as well as to identify any differences in profits before and after the market fire disaster. The methods used include multiple linear regression and the Wilcoxon rank-sum test to assess whether there are differences in traders' profits before and after the market fire. The results indicate that the variables of initial capital and business location have a positive impact on traders' profits. The difference test revealed a significant difference in profits before and after the market fire. The largest sum rank is in the negative rank, with a mean rank value of 41.07, indicating an average profit decrease of 40.07% after the fire at Weleri Central Market.